THE IMAGE OF JAVANESE WOMEN IN THREE NOVELS OF NANING PRANOTO - Sri Rahayu Nur Jayanti; Sudiati (Universitas Negeri Yogyakarta, 2023)
This research aims to describe the image, position, and problems of Javanese female characters in the three novels of Naning Pranoto. This research is descriptive qualitative with a feminist analysis approach. The sources of data are the novels entitled Lupa Singgah di Shizi, Wajah Sebuah Vagina, and Mei Merah 1998 (Kala Arwah Berkisah) by Naning Pranoto. The research data are all lingual units in the form of sentences that contain the image, position, and problems of Javanese women in Naning Pranoto’s three novels. Data were collected using reading and note-taking techniques. Data analysis was conducted by comparing, categorizing, presenting, and making inferences. The results of this study show that the image of women displayed in the three novels by Naning Pranoto is quite dynamic because of the social contact experienced by the characters. Each character's background also affects the image labeled towards Javanese female characters in the three novels. When viewed from the position of female characters, Javanese women in the novels are depicted as figures who are more dominated by men. This could be Naning Pranoto's intention to protest or show cynicism towards those who marginalize women. Then the next problems shown in the novel mostly start from economic problems that cause other problems to arise such as sexual violence, oppression, and marginalization.